2013
DOI: 10.1111/eci.12084
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and sibling recurrent risk of developmental dysplasia of the hip in Chinese population

Abstract: This study for the first time exhibits a high sibling recurrent risk and heritability for DDH in Asian population. It also shows there is a high probability to identify the underlying predisposition genes in future genetic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(63 reference statements)
1
14
1
3
Order By: Relevance
“…Femoroacetabular impingement in the hip joint and perinatal mechanical factors, such as breech presentation and swaddling, were confirmed as mechanical factors . Genetic factors, especially related gene disorders of cartilage metabolism, could also give rise to occurrence of DDH . Therefore, we speculate that these two major aspects may explain our results in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Femoroacetabular impingement in the hip joint and perinatal mechanical factors, such as breech presentation and swaddling, were confirmed as mechanical factors . Genetic factors, especially related gene disorders of cartilage metabolism, could also give rise to occurrence of DDH . Therefore, we speculate that these two major aspects may explain our results in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies examining the epidemiology of DDH within families using linkage approaches have demonstrated that heritable factors contribute between 50% and 85% of the total risk or liability of disease 3,26,27 , depending on population ancestry. Here, we used dense genome-wide genotyping data to estimate the heritable risk of DDH among unrelated individuals of UK European ancestry in the general English population.…”
Section: Discussionmentioning
confidence: 99%
“…DDH occurs in between 1 and 20 live births per 1,000 worldwide 44 , and predisposing factors include family history, being a first born, female sex and breech birth 45,46 . Familial segregation studies 47,48 suggest that DDH has a multifactorial genetic basis, but statistical support for this theory varies across populations and countries 49 . For example, in a Chinese population, the recurrent risk of DDH in the siblings of affected individuals was approximately tenfold greater than in controls and had a heritability of ~85% 47 .…”
Section: Ortolani Testmentioning
confidence: 99%
“…Familial segregation studies 47,48 suggest that DDH has a multifactorial genetic basis, but statistical support for this theory varies across populations and countries 49 . For example, in a Chinese population, the recurrent risk of DDH in the siblings of affected individuals was approximately tenfold greater than in controls and had a heritability of ~85% 47 . By contrast, the frequency of CHD varies between different dog breeds, reaching a peak of ~75% in Golden Retrievers and Rottweilers 50 , and shows no sex predilection in most breeds; the exception is Polish Tatra Sheepdogs, in which the risk of CHD in females is greater than threefold the risk in males 41 .…”
Section: Ortolani Testmentioning
confidence: 99%